2021
DOI: 10.21470/1678-9741-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Prolonged Ventilation Following Cardiac Surgery with Cardiopulmonary Bypass

Abstract: Introduction In this trial, we initially aimed to investigate the major predictive factors for prolonged mechanical ventilation (PMV) following cardiac surgery with cardiopulmonary bypass (CPB) in our center and, secondarily, we tried to find out the effects of the independent factors on mortality. Methods Between July 2017 and August 2018, 207 patients who underwent cardiac surgery with CPB were retrospectively investigated. The patients were randomly divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
9
0
5
Order By: Relevance
“…Only two studies have confirmed that leukocytosis is a risk factor for PMV after cardiovascular surgery, one had PMV ≥24 h after cardiac surgery with CPB, and the other had PMV ≥72 h after acute DeBakey type I aortic dissection surgery (45,46). Similar results were obtained; preoperative leukocytosis was an independent risk factor for two endpoints of PMV ≥24 h and ≥72 h in ATAAD after TAR.…”
Section: Discussionmentioning
confidence: 76%
“…Only two studies have confirmed that leukocytosis is a risk factor for PMV after cardiovascular surgery, one had PMV ≥24 h after cardiac surgery with CPB, and the other had PMV ≥72 h after acute DeBakey type I aortic dissection surgery (45,46). Similar results were obtained; preoperative leukocytosis was an independent risk factor for two endpoints of PMV ≥24 h and ≥72 h in ATAAD after TAR.…”
Section: Discussionmentioning
confidence: 76%
“…Tian et al compared the effects of remifentanil and sufentanil/fentanyl on the postoperative mechanical ventilation time of cardiac surgery patients, and found that remifentanil significantly shortened the postoperative mechanical ventilation time and reduced myocardial injury (16). Some researchers have confirmed that the use of sedation, and sucralfate, and the appropriate use of antibiotics reduces the risk of respiratory and related pneumonia after patients are transferred to the ICU after surgery, thereby avoiding PMV (17). Other studies have found that the use of invasive and non-invasive sequential mechanical ventilation effectively reduces the time of mechanical ventilation and reduces the incidence of respiratory complications (18,19).…”
Section: Discussionmentioning
confidence: 98%
“…The meta-analysis shows that PMV was significantly associated with the SAVR + CABG surgical operation. Longer CPB time is reported to be an independent predictor of postoperative respiratory failure [ 74 ] and PMV (> 24 h) [ 75 ]. Since SAVR + CABG operation has a CPB time longer than i-SAVR, we can argue that this factor might be determinant in increasing the incidence of postoperative PMV in patients who received CABG added to SAVR.…”
Section: Discussionmentioning
confidence: 99%